General Electric Pavilion
Caption, "General Electric Company The theme of the General Electric Company Pavilion is the ways in which electricity, put to use for human betterment is changing our world and our lives. The pavilion is topped by a 200 foot diameter dome, the dome is crowned with more than 1,000 lights providing a special night time effect in which the entire roof seems to turn. The lights are programmed in a sweeping, rotary motion, producing an impressive display of changing colors. On the second floor of the pavilion the show, "Carousel of Progress" dramatizes the contribution of electricity to the progress of better living in America, from the gay nineties to the Fair years."